Scanning electron microscopical examination of gonococcal urethral exudate. - Klein, R D (1977)
The relationship of gonococci and phagocytes in gonococcal urethral exudate was examined using a scanning electron microscope. Several stages in the phagocytic process were evident. These included pseudopodias, microvilli, and simple attachment of gonococci to phagocytic surfaces. Epithelial cells, also a part of the exudate, were examined in this study. Parallels are drawn between this and other phagocytic systems. The technique provides excellent preservation of phagocyte-bacterial interrelationships and offers a means of investigating the nature of the resistance of Neisseria gonorrhoeae to phagocytosis.